1994
DOI: 10.2527/1994.7271891x
|View full text |Cite
|
Sign up to set email alerts
|

Function of the hypothalamic-pituitary-adrenal axis and the sympathetic nervous system in models of acute stress in domestic farm animals2

Abstract: In response to stressors, the central nervous system of livestock (and other mammalian species) evokes physiological responses that ultimately result in activation of the hypothalamo-pituitary-adrenocortical (HPA) axis and the sympatho-adrenal axis. The responses of these major systems are presumed to have adaptive and homeostatic value during periods of stress. The major hormone regulating the synthesis and secretion of adrenal glucocorticoids is ACTH. In sheep, cattle, and pigs, both corticotropin-releasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(125 citation statements)
references
References 33 publications
4
112
0
9
Order By: Relevance
“…However, cortisol levels were still significantly increased after the removal of stress. This difference may be explained that 95% of salivary IgA is derived from salivary glands and stored in plasma cells as protein and released locally by the SNS stimuli of stress [2,15], while cortisol is a hormone derived from adrenal cortex through blood by the activation of hypothalamo-pituitary-adrenocortical (HPA) axis [16]. Moreover, previous reports suggested that salivary cortisol is highly variable and is responsive to a wide range of factors, and requires certain methodological prerequisites [9,29], but salivary secretory IgA is abundant in saliva and also exists as different form with serum IgA [15], and commercial kits for the specific measurement are available even in the domestic animal species such as pigs.…”
Section: Discussionmentioning
confidence: 99%
“…However, cortisol levels were still significantly increased after the removal of stress. This difference may be explained that 95% of salivary IgA is derived from salivary glands and stored in plasma cells as protein and released locally by the SNS stimuli of stress [2,15], while cortisol is a hormone derived from adrenal cortex through blood by the activation of hypothalamo-pituitary-adrenocortical (HPA) axis [16]. Moreover, previous reports suggested that salivary cortisol is highly variable and is responsive to a wide range of factors, and requires certain methodological prerequisites [9,29], but salivary secretory IgA is abundant in saliva and also exists as different form with serum IgA [15], and commercial kits for the specific measurement are available even in the domestic animal species such as pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have described different factors that could affect horse performance during show jumping competitions (Clayton and Barlow, 1989;Bartolomé et al, 2008). When the influence of any of these factors (or a combination of them) induces activation of the sympatho-adrenal (ANS) medullary system, the hypothalamo-pituitary-adrenocortical (HPA) axis and/or an emotional reaction, they induce a stress response (Dantzer and Mormède, 1983;McMillan, 2005;Von Borell et al, 2007) and thus they can be termed as stressors (Minton, 1994). Hence, stress may be defined as the homeostatic, physiological and behavioural responses detectable in an animal as a result of interactions with environmental stressors (Stephens, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Stress is commonly considered to restrain the immune system and may be responsible for an increase in the occurrence of disease in the presence of a pathogen. It has been stated that the pituitary adrenocorticotropic hormone travels through the blood to the adrenal cortex, where cells of the zona fasciculata secrete glucocorticoids (32), with cortisol being the principal glucocorticoid in swine and cattle (33). Stress hormones released in response to the activation of the hypothalamic-pituitary-adrenal axis (CRF, ACTH, and cortisol) have been indicated to have an effect on aspects of the immune system (34).…”
Section: Discussionmentioning
confidence: 99%